a) 11x + 10 = 2x + 37
11x - 2x = 37 - 10
9x = 27 /:9
x = 3
b) 12x + 6 = 9x + 12
12x - 9x = 12 - 6
3x = 6 /:3
x = 2
c) 10x + 16 = 3x + 2
10x - 3x = 2 - 16
2x = -14 /:2
x = -7
d) 13x + 30 = 21x + 14
13x - 21x = 14 - 30
-8x = -16 /:(-8)
x = 2
a) 5x - 12 = 4 + 4x
5x - 4x = 4 + 12
x = 16
b) 9x - 8 = 3x + 2
9x - 3x = 2 + 8
6x = 10 /:6
x = 10/6
x = [tex]\frac{5}{3}[/tex]
x =[tex]1\frac{2}{3}[/tex]
c) 10x - 4 = 5x + 8
10x - 5x = 8 + 4
5x = 12 /:5
x = [tex]\frac{12}{5}[/tex]
x = [tex]2\frac{2}{5}[/tex]
d) 2x - 2 = -12x + 18
2x + 12x = 18 +2
14x = 20 /:14
x = [tex]\frac{20}{14}[/tex]
x = [tex]\frac{10}{7}[/tex]
x = [tex]1\frac{3}{7}[/tex]